SERVANT LEADERSHIP OF THE HEAD OF THE MADRASAH IN IMPROVING TEACHER PERFORMANCE AT AL-WASHLIYAH PRIVATE ALIYAH MADRASAH MEDAN DISTRICT MEDAN CITY AREA - Rina Hidayah Tambusai; Muhammad Rifa'i; Marasamin Lubis (Pena Cendekia Insani, 2025)
This study aims to analyze the servant leadership of madrasah heads in improving teacher performance at Al-Washliyah Private Aliyah Madrasah, Medan Area District, Medan City. This study uses a qualitative approach with case studies to explore the leadership role of madrasah heads in improving teacher performance. This study used 9 informants as primary data that were selected purposively. Data were collected through non-participant observations, semi-structured interviews, and documentation studies. The validity of the data is maintained by triangulation techniques, comparing data from interviews, observations, and documentation to ensure the validity and accuracy of the findings. The results of this study show that the decline in teacher performance at the Al-Washliyah Private Aliyah Madrasah Medan Area is caused by the leadership crisis of the madrasah head, which can be seen from the physical and emotional absence of the madrasah head, lack of supervision, and hampered communication. The absence of consistent evaluation and reward also reduces teachers' motivation and self-efficacy, as well as affects their professional and spiritual development. The application of servant leadership by the head of the madrasah is very relevant and effective to overcome this problem, because the concept emphasizes the leader as a servant who listens, provides support, and facilitates teacher development. By applying principles such as empathy, collaboration, and recognition, madrasah heads can create a positive work climate and support teacher performance improvement. Supporting factors in improving teacher performance include humanist and visionary leadership, as well as fostering supervision and evaluation, while the main inhibiting factors are passive, bureaucratic leadership styles, lack of communication, and lack of consistent rewards.